2018
DOI: 10.3390/su10114003
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences and Welfare Evaluation under Current Food Inspection Measures in China: Evidence from Real Experiment Choice of Rice Labels

Abstract: Frequent food quality and safety issues result in various food inspection measures in China, while some are not widely acknowledged by the public and are less efficient. Consumer demand is significant for priority setting in food policy. This study investigates Chinese consumers' heterogeneous preferences for selected food inspection measures and estimates welfare effects based on willingness-to-pay (WTP) calculation. Rice consumption data from a 2018 nationwide consumer survey designed using the real choice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This could be due to rice being the staple food in China; therefore, consumers have considerable familiarity with this kind of food. As mentioned previously [ 68 ], plant products in China are consumed in larger quantities and at higher frequencies, among of which rice is likely to be the most typical plant product that faces serious food quality and safety issues. The foods where the certification logos were least related to the perception of safety were fish and milk.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to rice being the staple food in China; therefore, consumers have considerable familiarity with this kind of food. As mentioned previously [ 68 ], plant products in China are consumed in larger quantities and at higher frequencies, among of which rice is likely to be the most typical plant product that faces serious food quality and safety issues. The foods where the certification logos were least related to the perception of safety were fish and milk.…”
Section: Discussionmentioning
confidence: 99%
“…A cost-leadership strategy may also potentially reduce the benefits gained from green process innovation, since cost-leaders engage in fewer activities of communicating their green images in the market [30]. We suggest that firms which adopt cost-leadership strategies can gain support from stakeholders by achieving certification by third-party auditors [72]. For example, Terlaak and King [73] found that ISO 14001 can be a signal of environmental responsibility which helps firms benefit from their improved green production processes.…”
Section: Cost-leadership Strategymentioning
confidence: 97%
“…Currently, the government, mainly the CFDA and its subordinates, have imposed comprehensive supervision of the food supply chain. In China, most food safety problems are found in food safety sampling inspection, spot checking, specialized inspection, and unannounced inspection by the government [39,48]. Therefore, the government and third parties should strengthen their supervision over the food supply chain, issue strict regulations and standards, conduct strict food safety inspections, and levy more severe punishments for irregularities [12,48].…”
Section: Implications and Limitationsmentioning
confidence: 99%